Lewis Mumford : a life - Miller, Donald L. ([Pittsburgh] : University of Pittsburgh Press, 1989)
Based on ten years of research and unprecedented access to original and private papers, this is an engagingly written study of Lewis Mumford's full and fascinating life. It examines his life as one of the 20th century's most important American intellectuals and his contributions to history; philosophy; literary, art, and architectural criticism; urban planning; and the study of technology. He was perhaps the world's foremost authority on cities, architecture, and technology, as well as receiving nearly every major intellectual award, including the National Medal for the Arts
Preface : call me Jonah! -- A solitary tree -- A New York boyhood -- A Jovian father -- A man in the making -- Son of Mannahatta -- A Grub Street apprenticeship -- Sophiology -- New York again -- Beyond Utopia -- Architecture as a home for man -- New towns for America -- Libra -- Golden days -- A period in purgatorio -- Crisis and opportunity -- The renewal of life -- Love and work -- One more love -- The culture of cities -- From lover to monk -- The barbarian eruption -- The primacy of the person -- The age of frustration -- Cities of men -- The endangered city -- Harvest time -- The myth of the machine -- The Amenia years
Keywords: Mumford, Lewis, -- 1895-1990.; Social reformers -- Biography -- United States; City planners -- Biography -- United States; Architects -- Biography -- United States